Demographics, natural history and treatment outcomes of non‐molar gestational choriocarcinoma: a UK population study. (3rd April 2020) - Savage, P; Winter, M; Parker, V; Harding, V; Sita‐Lumsden, A; Fisher, RA; Harvey, R; Unsworth, N; Sarwar, N; Short, D; Aguiar, X; Tidy, J; et al.
Abstract : Objective: To investigate the demographics, natural history and treatment outcomes of non‐molar gestational choriocarcinoma. Design: A retrospective national population‐based study. Setting: UK 1995–2015. Population: A total of 234 women with a diagnosis of gestational choriocarcinoma, in the absence of a prior molar pregnancy, managed at the UKs two gestational trophoblast centres in London and Sheffield. Methods: Retrospective review of the patient's demographic and clinical data. Comparison with contemporary UK birth and pregnancy statistics. Main outcomes: Incidence statistics for non‐molar choriocarcinoma across the maternal age groups. Cure rates for patients by FIGO prognostic score group. Results: Over the 21‐year study period, there were 234 cases of non‐molar gestational choriocarcinoma, giving an incidence of 1:66 775 relative to live births and 1:84 226 to viable pregnancies. For women aged under 20, the incidence relative to viable pregnancies was 1:223 494, for ages 30–34, 1:80 227, and for ages 40–45, 1:41 718. Treatment outcomes indicated an overall 94.4% cure rate. Divided by FIGO prognostic groups, the cure rates were low‐risk group 100%, high‐risk group 96% and ultra‐high‐risk group 80.5%. Conclusions: Non‐molar gestational choriocarcinoma is a very rare diagnosis with little prior detailed information on the demographics and natural history. The data in this study give age‐related incidence data based on a large national population study. The results also demonstrated the widely varying natural history of this rare malignancy and the marked correlation of disease incidence with rising maternal age. Tweetable abstract: National gestational choriocarcinoma database indicates a close association between increasing maternal age and incidence. Tweetable abstract: National gestational choriocarcinoma database indicates a close association between increasing maternal age and incidence.